Bachelard’s concept of science - Zakari , Khalida (Journal of Social Sciences and Humanities, 2023)
Gaston Bachelard rejects the cumulative view in science that science develops according to a path of accumulation and accumulation of information, because scientific progress takes place through the conflict between the new and the old and he acknowledges the rejection of the two ideas of communication and the absolute in science. In realizing the structure of science, Bachelard used methodological tools by which he analyzes the structure of scientific thought and considers them scientific means that allow us to realize the true path of science. It is the logic of the development of science, which is constantly rebuilding its foundations, and here is crystallizing the audacity of the epistemological rupture created by Bachelard, which rejects the progress of scientific knowledge in a line based on the accumulation and accumulation of information. New looks. Contemporary epistemological research that was associated with Başlar in its core is a critical analytical work on the foundations of scientific knowledge by constantly examining and reviewing its principles. Here, as Bachelard's scientific process is manifested, he considers that the obstacles are the result of a realistic origin and to overcome them there must be a rational combination. He tries to say that all scientific errors resulted from the poor application of scientific methods. Bachelard used psychoanalysis as a methodological tool to analyze the nature of scientific knowledge, discover the repressions of science, and trace the various stages that science goes through in its psychological journey. Therefore, if Bachelard spoke about psychoanalysis, he did not test a theory in terms of whether it is scientific or not, but rather took it as a mechanism.